2019
DOI: 10.3390/app9163384
|View full text |Cite
|
Sign up to set email alerts
|

A Subjective Study on User Perception Aspects in Virtual Reality

Abstract: Three hundred and sixty degree video is becoming more and more popular on the Internet. By using a Head-Mounted Display, 360-degree video can render a Virtual Reality (VR) environment. However, it is still a big challenge to understand Quality of Experience (QoE) of 360-degree video since user experience during watching 360-degree video is a very complex phenomenon. In this paper, we aim to investigate four QoE aspects of 360-degree video, namely, perceptual quality, presence, cybersickness, and acceptability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To a large extent, VR can increase the sense of presence and situational awareness [26]. Therefore, it represents an optimal platform to provide unique immersive experiences for users [27,28] and to support sense-making with visualizations [29] and social interaction for group activities. However, its effectiveness depends heavily on how the virtual workspace(s), whether for individuals or the whole group, and collaborative interactions are provided, as a poor design may harm the collaboration and exploratory process [4].…”
Section: Collaboration With Visual-spatial Information In Vr Environmentsmentioning
confidence: 99%
“…To a large extent, VR can increase the sense of presence and situational awareness [26]. Therefore, it represents an optimal platform to provide unique immersive experiences for users [27,28] and to support sense-making with visualizations [29] and social interaction for group activities. However, its effectiveness depends heavily on how the virtual workspace(s), whether for individuals or the whole group, and collaborative interactions are provided, as a poor design may harm the collaboration and exploratory process [4].…”
Section: Collaboration With Visual-spatial Information In Vr Environmentsmentioning
confidence: 99%
“…Zerman et al [53] presented a behaviour analysis of users interacting with colored volumetric media in a AR application. Tran et al [48] suggested that, in case of evaluating video quality in an immersive setup, aspects such as cybersickness and presence should not be overlooked. Recently, an evaluation of static point cloud contents was conducted in a VR environment [9].…”
Section: Quality Assessment For Point Cloudsmentioning
confidence: 99%
“…Standardization of streaming 360-degree video is in progress. Recently, Curcio et al [43] have adapted ITU-T 2D and 3D video testing recommendations to 360-degree video in VR HMD, Tran et al [44] have assessed and categorized QoE aspects that affect 360-degree video streaming, and Pérez and Escobar [45] have proposed an assessment-aiding tracking tool for an upcoming ITU-T Recommendation for 360-degree VR video, ITU-T Rec. P.360-VR [46].…”
Section: Quality Of Experience For Virtual Augmented Environmentsmentioning
confidence: 99%